Meta Analysis the Effect of Acupuncture Therapy on Pain Reduction in Osteoarthritis Patients - Susilo, Fahmi Eko; Kristiyanto, Agus; Prasetya, Hanung (Indonesian Journal of Medicine, 2021)
Background: Osteoarthritis (OA) is the most common joint condition and is characterized by progressive erosion of the articular cartilage. Based on data from Basic Health Research (2018) the prevalence of joint disease in Indonesia is recorded at around 7.3% and osteoarthritis (OA) or arthritis is a common joint disease. As the two main non-surgical methods, physiotherapy and acupuncture have been shown to be safe and effective in the therapy of osteoarthritis.Subjects and Method: This was a systematic review and meta-analysis study. The articles used in this study were obtained from several databases including PubMed, Google Scholar, and Springer Link. The articles used in this study were those published from 2000-2020. The article search was carried out by considering the eligibility criteria defined using the PICO model. The population in the study were patients with osteoarthritis complaints with intervention in the form of acupuncture therapy, the comparison was the sham acupuncture outcome in the form of pain reduction. The keywords for finding articles are as follows: "Acupuncture" OR "Osteoarthritis" AND "Randomized Controlled Trials". The articles included in this study are full text articles with an observational study design. Articles were collected using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 9 articles were reviewed in this study. A meta-analysis of 9 randomized control trials showed that acupuncture therapy reduced pain in osteoarthritis patients (SMD= -0. 49; 95% CI= -0.88 to -0.10; p= 0.01).Conclusion: Acupuncture therapy reduces pain in osteoarthritis patients.Keywords: acupuncture, osteoarthritis, acupuncture osteoarthritis, randomized control trialCorrespondence: Fahmi Eko Susilo. Masters Program in Public Health. Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: fahmiekss@gmail.com. Mobile: 081393644991.Indonesian Journal of Medicine (2021), 06(01): 95-103https://doi.org/10.26911/theijmed.2021.06.01.10.